Fostering diversity in healthcare: The UDOC summer enrichment experience - Coler, Celeste; A. J. Balatico; Jasmine Gault; Nicole Hinds; Nora Coronado; Estell Williams (American Journal of STEM Education, 2025)
A more diverse healthcare workforce is critical to improving the quality of care offered to diverse populations. Residential enrichment programs represent a promising strategy for diversifying the healthcare workforce. UDOC is a 5-week residential summer enrichment program hosted by the University of Washington that aims to inspire, affirm, and nurture underrepresented high school students’ interest in healthcare professions by exposing them to various health-related topics and skills. Through interviews with fourteen program alumni, this study explores the impact of UDOC on students’ personal, academic, and professional growth, and how the program influenced their subsequent academic and career choices. Reporting the long-term outcomes of UDOC alumni provides valuable insights that underscore the importance of such programs in fostering diversity within health professions.